2016
DOI: 10.1002/2015gl067097
|View full text |Cite
|
Sign up to set email alerts
|

Seismological detection of low‐velocity anomalies surrounding the mantle transition zone in Japan subduction zone

Abstract: In the Japan subduction zone, a locally depressed 660 discontinuity has been observed beneath northeast Asia, suggesting downwelling of materials from the mantle transition zone (MTZ). Vertical transport of water‐rich MTZ materials across the major mineral phase changes could lead to water release and to partial melting in surrounding mantle regions, causing seismic low‐velocity anomalies. Melt layers implied by low‐velocity zones (LVZs) above the 410 discontinuity have been detected in many regions, but seism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
82
1
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 67 publications
(96 citation statements)
references
References 48 publications
(88 reference statements)
6
82
1
1
Order By: Relevance
“…The released water by the decomposition of ShyB will migrate upward and promote the partial melt to reduce the sound velocity at shallower depth (Figure ). Liu et al [] indeed observed the low‐velocity zones just above 800 km discontinuity beneath Changbaishan volcanic area and proposed that the water comes from metallic iron. This interpretation requires that the metallic iron is only stable in the uppermost lower mantle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The released water by the decomposition of ShyB will migrate upward and promote the partial melt to reduce the sound velocity at shallower depth (Figure ). Liu et al [] indeed observed the low‐velocity zones just above 800 km discontinuity beneath Changbaishan volcanic area and proposed that the water comes from metallic iron. This interpretation requires that the metallic iron is only stable in the uppermost lower mantle.…”
Section: Discussionmentioning
confidence: 99%
“…Several locally hydrous transition zones have also been suggested by geophysical observations such as high V p / V s at the mantle transition zone above stagnant Japan slab [ Li et al ., ], high electrical conductivity beneath northeast China [ Karato , ], and low‐velocity anomalies on top of the Tonga slab at the transition zone depth [ Savage , ]. Furthermore, water‐induced partial melt was generally thought to be the main cause for low‐velocity anomalies beneath North America [ Schmandt et al ., ] and Japan slab [ Liu et al ., ] at a depth around 730–770 km, which suggests that the water may even have been transported into the lower mantle.…”
Section: Introductionmentioning
confidence: 99%
“…The LVL‐410 was initially discovered beneath northeast Asia by Revenaugh and Sipkin [] using seismic waves reflected at the core‐mantle boundary (multiple‐ ScS reverberation). Later seismic studies using a similar technique [ Courtier and Revenaugh , ; Bagley et al , ], receiver functions [ Vinnik and Farra , ; Vinnik et al , ; Fee and Dueker , ; Jasbinsek and Dueker , ; Vinnik and Farra , ; Wittlinger and Farra , ; Leahy , ; Jasbinsek et al , ; Schaeffer and Bostock , ; Tauzin et al , ; Vinnik et al , ; Schmandt et al , ; Huckfeldt et al , ; Bonatto et al , ; Morais et al , ; Thompson et al , ; Liu et al , ], and body wave triplications [ Song et al , ; Gao et al , ; Obayashi et al , ] suggest the widespread existence of this LVL (Figure and supporting information Table S1). In addition, an electromagnetic study in the southwestern U.S. also suggests a layer with high conductivity near the 410 km discontinuity [ Toffelmier and Tyburczy , ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous observations of an LVL‐410 under continents and continental margins [ Revenaugh and Sipkin , ; Vinnik and Farra , ; Vinnik et al , ; Fee and Dueker , ; Song et al , ; Gao et al , ; Obayashi et al , ; Courtier and Revenaugh , ; Jasbinsek and Dueker , ; Toffelmier and Tyburczy , ; Vinnik and Farra , ; Wittlinger and Farra , ; Bagley et al , ; Leahy , ; Jasbinsek et al , ; Schaeffer and Bostock , ; Tauzin et al , ; Vinnik et al , ; Schmandt et al , ; Huckfeldt et al , ; Tauzin et al , ; Bonatto et al , ; Morais et al , ; Thompson et al , ; Liu et al , ]. Digits indicate the reference numbers listed in supporting information Table S1.…”
Section: Introductionmentioning
confidence: 99%
“…The epicentral move-out of a direct phase differs from a reverberated phase [e.g., . To aid the identification of stable converted phases, we compute jackknife uncertainties [e.g., Efron, 1982;Leahy and Collins, 2009;Liu et al, 2016]. Using the unrotated vertical (Z) and radial (R) components of station T06, the jackknife uncertainties of epicentral-bin stacks are large ( Figure 2) and only when we use a larger number of traces per bin do the plotted RF traces become stable (see also Figure 3).…”
Section: Stations With Sediment Resonancementioning
confidence: 99%